Facilitated Peptide Transport via the Mucosal Epithelium: Impact on Tolerance Induction - Kenngott, Elisabeth E.; Pfeil, Jennifer; Hoffmann, Ute; Lauer, Uta; Kühl, Anja A.; Rigby, Anne; Pernthaner, Anton; Hamann, Alf (Frontiers in Immunology, 2017)
A hallmark of autoimmunity is the breakdown of tolerance and generation of effector responses against self-antigens. A hallmark of autoimmunity is the breakdown of tolerance and generation of effector responses against self-antigens. Re-establishment of tolerance in autoimmune disorders was always the most desired treatment option; however, despite many efforts, clinical trials have been largely unsuccessful. This also applies to the generation of oral tolerance, which seems to be a default response type of the mucosa-associated lymphoid tissues (MALT) to harmless antigens. In this study we report improved efficacy of oral tolerance induction by coupling antigen with the newly identified mucosal carrier peptide 13C. Antigen coupled to 13C is efficiently taken up in the gastrointestinal tract and could be visualized in cells of the lamina propria. Oral, rectal or nasal treatment effectively induced the proliferation of antigen-specific T cells with some increase in the frequency of regulatory T cells. In a model of delayed type hypersensitivity, especially intrarectal tolerization treatment resulted in reduced footpad swelling, demonstrating a moderate tolerogenic effect of mucosal treatment with 13C coupled antigen. Coupling of antigens to a transmucosal carrier therefore is a promising tool to improve the efficacy of vaccination via mucosal surfaces.